Ten Years of Pediatric Lung Ultrasound: A Narrative Review - Musolino, Anna Maria; Tomà, Paolo; De Rose, Cristina; Pitaro, Eugenio; Boccuzzi, Elena; De Santis, Rita; Morello, Rosa; Supino, Maria Chiara; Villani, Alberto; Valentini, Piero; Buonsenso, Danilo (Frontiers in Physiology, 2022)
Lung diseases are the most common conditions in newborns, infants, and children and are also the primary cause of death in children younger than 5 years old. Traditionally, the lung was not thought to be a target for an ultrasound due to its inability to penetrate the gas-filled anatomical structures. With the deepening of knowledge on ultrasound in recent years, it is now known that the affected lung produces ultrasound artifacts resulting from the abnormal tissue/gas/tissue interface when ultrasound sound waves penetrate lung tissue. Over the years, the application of lung ultrasound (LUS) has changed and its main indications in the pediatric population have expanded. This review analyzed the studies on lung ultrasound in pediatrics, published from 2010 to 2020, with the aim of highlighting the usefulness of LUS in pediatrics. It also described the normal and abnormal appearances of the pediatric lung on ultrasound as well as the benefits, limitations, and possible future challenges of this modality.